Tolerance and empathy as displays of spirituality of the person at the receiving party in polycultural space - T V Chykvadze (Peoples' Friendship University of Russia (RUDN University), 2010)
In the article are analyzed the manifestations of spirituality: tolerance and empathy, which are the basis for creating friendly atmosphere for adaptation of foreign students. Also are investigated their correlations, gender differences and differences between students of natural-science and humanitarian direction.